Konkurencyjność eksportu polskiego przemysłu mięsnego na tle UE-15 - Menart, Łukasz; Juchniewicz, Małgorzata (Competitiveness of Polish Meat Industry Against the Background of UE-15, 2006)
The aim of the paper is the appreciation of competitiveness of Polish meat industry against the UE-15 countries from 2000 till 2004. The study concerns three types of products which belong to meat industry. To analyse tchem the author uses international competitiveness indicators. The study proves that Polish meat industry is competitive in confrontation with UE and it has chances to grow in the future.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 2, s. 86-92